FINTECH ADOPTION FOR MSMES SUSTAINABILITY - Arifin, Agus Zainul; Natsir, Khairina; Darryl, Darryl; Janet, Janet (International Journal of Application on Economics and Business, 2025)
During the COVID-19 pandemic, SMEs in Indonesia faced serious challenges due to temporary or permanent business closures as a result of the SMEs policy and the resulting economic crisis. Decreased sales and difficulties in securing funding have been the main problems faced by SMEs. To overcome these challenges, the use of Financial Technology (Fintech) is emerging as a promising solution. Fintech Lending Service provides an opportunity for MSMEs to obtain much-needed funding loans, while Fintech Digital Payment System provides an alternative transaction method that is more efficient. The study purposes is to aiming to examine the relationship between the adoption of Fintech Lending Service and Fintech Digital Payment System with MSME performance.This study uses the Diffusion of Innovation theory approach and PLS-SEM data analysis method, the source of data is from questionaire and collected 204 data from the population. The results of the study are expected to provide valuable insights into how financial technology can support the viability of SMEs amid economic uncertainty. The novelty of this research is combining the separate fintech digital payment and lending service research into one research.